Comments from the Editors - Tulay Girard; Brian Whelan (Journal of Applied Marketing Theory)
Welcome to the Spring 2025 issue of the Journal of Applied Marketing Theory. The Journal of Applied Marketing Theory (JAMT) is dedicated to providing a reputable platform for the dissemination of academic research that both advances marketing knowledge and offers practical insights for marketing professionals.